Predicting Modelling of Factors Influencing Innovative Work Behavior - Supriyanto, Achmad Sani; Ekowati, Vivin Maharani; Sofyan Aldi, (Technium Social Sciences Journal, 2020)
The hospital success depends on the human resources. Hospital operational system can run well because of human resources support. Therefore, the hospital needs to empower human resources to achieve the organizational goals. One of the solutions is to initiate the Innovative Work Behavior. This study aims to examine the direct effect of work environment on Innovative Work Behavior and the effect of work environment on Innovative Work Behavior through work motivation. This study uses quantitative research. Data analysis uses the PLS (Partial Least Square). The population was all 200 employees or Malang Public Hospital. The sampling technique uses Simple Random Sampling, so the number of samples used is 133 employees. Data was collected by questionnaire. The study results indicated that work environment has a direct effect on Innovative Work Behavior and work environment has a indirect effect on Innovative Work Behavior through work motivation.